Statut bucco-dentaire au sein d’une population gériatrique libanaise : étude pilote - Nada FARHAT MCHAYLEH; Nada EL-OSTA; Rafif SLEIMAN; Joyce TANNOUS; Hani TOHMÉ; Paul BOULOS (International Arab Journal of Dentistry (IAJD), 2011)
According to the World Health Organization (WHO), oral health status represents an indicator of the physical and psychological general state of a person, especially among the elderly. Many epidemiological studies have studied oral health among the geriatric population. In Lebanon, the lack of publications related to this subject encouraged us to realize a pilot study in order to evaluate oral health status among a Lebanese geriatric sample from low socioeconomic class. This study was conducted in a volunteer associational center (“Resto du Coeur”), by the Department of ediatric and community dentistry, in collaboration with the Department of prosthodontics of the Faculty of Dental Medicine, at Saint-Joseph University, Lebanon. This activity included the oral health evaluation of 51 geriatric persons along with educational oral health promotion.The oral exam of the participants showed a high prevalence of edentulism, a poor oral hygiene as well as multiple periodontal and dental problems.